The Digital Humanities and Literary Studies - Eve, Martin Paul (Oxford University Press, 2022)
This book delivers an introduction and overview of developing intersections between digital methods and literary studies. The Digital Humanities and Literary Studies serves as a starting place for those who wish to learn more about the possibilities, and the limitations, of the oft-touted digital humanities in the literary space. The volume engages with the proponents of digital humanities and its detractors alike, aiming to offer a fair and balanced perspective on this controversial topic. The book combines a survey and background approach with original literary research and, therefore, straddles the divide between seasoned digital experts and interested newcomers.